2017
DOI: 10.1080/17470919.2017.1403374
|View full text |Cite
|
Sign up to set email alerts
|

It’s not me, it’s you - Differential neural processing of social and non-social nogo cues in joint action

Abstract: This study used a joint flanker task to investigate differences in processing of social and non-social nogo cues, i.e., between cues indicating that a co-actor should respond and cues signaling that neither actor nor co-actor should respond, using event-related potentials (ERPs) and trial-to-trial response times (RTs). It was hypothesized that a social co-actor's response should be reflected in stronger modulation (slower RTs on subsequent trials; augmented neural responses) for social compared to non-social n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…While Experiments 1 and 2 thus provide consistent evidence in favor of a Pavlovian bias in observational learning which is comparable to the one in active learning, both experiments did not comprise a manipulation check to determine if the observational learners had actually believed to be watching an active subject’s performance. Since there is a growing body of evidence that social contextual factors such as the presence of an uninvolved observer (Voegler et al, 2018 ), the representation of the task set of another individual during task sharing (Peterburs et al, 2019 ), or the degree of familiarity between subjects (Morelli et al, 2018 ) affect performance monitoring and reward processing for own and observed behavior, we decided to run a follow-up experiment that involved simultaneous testing of pairs of subjects, with one individual as the active and the other as the observational learner.…”
Section: Methodsmentioning
confidence: 99%
“…While Experiments 1 and 2 thus provide consistent evidence in favor of a Pavlovian bias in observational learning which is comparable to the one in active learning, both experiments did not comprise a manipulation check to determine if the observational learners had actually believed to be watching an active subject’s performance. Since there is a growing body of evidence that social contextual factors such as the presence of an uninvolved observer (Voegler et al, 2018 ), the representation of the task set of another individual during task sharing (Peterburs et al, 2019 ), or the degree of familiarity between subjects (Morelli et al, 2018 ) affect performance monitoring and reward processing for own and observed behavior, we decided to run a follow-up experiment that involved simultaneous testing of pairs of subjects, with one individual as the active and the other as the observational learner.…”
Section: Methodsmentioning
confidence: 99%
“…In a large sample of PD patients and HCs, we found that cognitive ToM was associated with a joint Flanker effect. When all participants were arbitrarily categorized into individuals with high or low scores in the AT test, we found that PD patients with high scores exhibited a joint Flanker effect (Atmaca et al, 2011;Peterburs et al, 2017), whereas patients with low scores did not. As shown in Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, the joint action effect has been found in healthy participants using other types of stimulus-response mapping and interference tasks, such as the Flanker task (Atmaca, Sebanz, & Knoblich, 2011;Peterburs, Liepelt, Voegler, et al, 2017); this suggests how the Flanker paradigm is a promising candidate for further scrutinizing joint action, considering that the (Eriksen) Flanker task incorporates response conflict as does the Simon task, and that in this task the interference arises from short-lived stimulus-response assignments that are arbitrary and categorical (and not based on spatial features). In its standard version of the task (as created by Eriksen & Eriksen, 1974), participants respond to different targets by pressing one of two different keys (e.g., the key on the left when K or H appear, and the key on the right when C or S are presented), while targets are surrounded by distracting flankers, which can be (1) identical to the target (e.g., KKKKK; identical trials), (2) perceptually different from the target but referring to the same response (e.g., HHKHH; compatible trials), (3) perceptually different from the target and referring to the opposite response (e.g., SSKSS; incompatible trials), and (4) perceptually different from the target without referring to any response (e.g., UUKUU; neutral trials).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations